Pattern of homicidal deaths autopsied at Victoria Hospital, Bangalore – A one-year study - Sumangala , C N; Raksha, L; Venkata Raghava, S (Journal of Indian Academy of Forensic Medicine, 2019)
Homicide is the outrageous and the severest form of violent crime, where one human being divests another human being of the fundamental right to live. The rate of homicidal deaths is considered the most representative crime indicator. The present study attempts to analyze the recent trend of the homicidal deaths and it’s demographic, social and medico-legal aspects in one of the major cities of Karnataka state. The study was carried out for 1 year (2017) in the Department of Forensic Medicine, tertiary care hospital attached to a medical college. The cases brought to the department for medico-legal autopsy either confirmed or later registered as homicide by investigating police officer were considered for the study. Homicidal deaths constituted 2.2% of the total autopsies done rd th st where the majority of victims belonged to 3 and 4 decades of life with male predomination in all age groups except for 1 decade. Maximum victims were assassinated at the street during the afternoon and late evening. The main motive was revenge in 89.5% of cases. Sharp weapon injuries (38%) were the commonest pattern of death followed by blunt weapon injuries (25%).